PENGGUNAAN DIAPERS MEMPERLAMBAT KESIAPAN TOILET TRAINNING PADA TODDLER - Nurul Kamariyah; Mutmilah Tukhusnah (Jurnal Ilmiah Kesehatan, 2013)
Toddlers should have been done the training to use the toilet, but in fact there were many mothers who did not teach about toilet training to her children because of that her children were still not able to implementation toilet training. Therefore, the research was purposed to analyze the relationship between the diapers using and the readiness of toilet training in toddler in RW 04 Keboan Anom village Gedangan district Sidoarjo regency. The design applied in this research was analytic cross sectional. The population involved 56 mothers having babies 18-36 months old in RW 04 Keboan Anom village Gedangan district Sidoarjo regency in which 49 respondents were taken as the samples by using the simple random sampling technique. The independent variable of this research is diapers using and dependent variable is the readiness of toilet training in toddler Moreover, the instruments used to collect the data were questionnaires. The collected data were then analyzed by applying Spearman’s Rank test with the level of significance α = 0,05. The results of research showed that nearly half of the 49 respondents (46.9%) use the diapers for 12-24 hours / day to her children and the majority (53.1%) had poor toilet training readiness. Based on result of the statistical test, it showed that ρ = 0,000 which meant that ρ < α = 0,05 so that H0 was rejected. Thus, it also proved that there was a relationship between the use of diapers and the readiness of toilet training in toddler. In conclusions, the higher frequency use of diapers can result in the bad effect for the child, they will have a lack toilet training readiness. The medics are expected to be more frequent for providing information about toilet training and for parents, they need to increase the guidance and the direction about toilet training to their children.